Psychological Well-Being of Teacher Professional Education Program (TPEP) Students: A Demographic Analysis - Desi Nurwidawati; Miftakhul Jannah; Rizky Putra Santosa; Arfin Nurma Halida; Ainul Fahmiya; Nabila Rachman; Kususanto Ditto Prihadi; Elok Faiqoh Maulidiyah; Fatkur Rohman Kafrawi; Faridha Nurhayati; Muhammad Reza (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This research aims to analyze the distribution of several demographic aspects of teacher professional education program (TPEP) students and explore the differences in psychological well-being in demographic aspects. Method: This research is quantitative. Participants were 816 teacher professional education program students who were obtained using purposive sampling techniques. The inclusion criteria for research participants are 1) teacher professional education program students and 2) willingness to become research participants and follow the process until completion. Data analysis uses the statistic descriptive. Data was analyzed using JASP software. Results: The results of this study present the demographic profile of TPEP students, which is categorized into several aspects. It was found that most TPEP students are women, while the dominant age of TPEP students is 21-24 years. In addition, most students are unmarried, and honorary teachers have a varied distribution of work experience. In this research, the analysis of differences in psychological well-being in demographic aspects is supported by previous research findings. Novelty: This study presents the demographic distribution of TPEP students, which can be used to develop psychosocial support through demographic characteristics to improve psychological well-being effectively.